A comparative study of photovoltaic performance between non-fullerene and fullerene based organic solar cells. Issue 49 (3rd May 2016) - Jiang, Bo; Zhang, Xin; Zheng, Yuanhui; Yu, Gui; Yao, Jiannian; Zhan, Chuanlang
Abstract : A perylene diimide dimer based non-fullerene acceptor shows a promising efficiency of 5.24% and 6.36% with PBDTTT-C-T and PBDT-TS1 as the donor, respectively. Abstract : Herein, we synthesized a perylene diimide dimer as an efficient non-fullerene acceptor, which gives a promising efficiency of 5.24% and 6.36% with PBDTTT-C-T and PBDT-TS1 as the donor, respectively. A comparative study on the photovoltaic performance of the non-fullerene and fullerene based solar cells clearly demonstrates that relatively stronger recombination loss of the free carriers, lower electron mobility and larger phase size account for the lower short-circuit current density of the non-fullerene based solar cell.